EN The combined effect of heating zone length and inclination angle on start-up, transient and operational characteristics of pulsating heat pipe - К. Мане; Є.С. Алексеїк (Holodilʹnaâ Tehnika i Tehnologiâ)
Pulsating heat pipes (PHP) are novel heat transfer devices which have wide prospects of application in energy, refrigeration, cryogenic systems and electronics cooling because of simple design and high efficiency of heat transfer. However, heat transfer characteristics of PHP depend on many parameters. This paper is dedicated to experimental investigation of the impact of heating zone length and angle of inclination on the start-up and operational characteristics of PHP. The investigation involved a systematic variation of the heating zone length and inclination angle with measuring of key performance indicators, including start-up heat flux density and temperature, transient heat flux density, and thermal resistance, for water, methanol and pentane as a heat carrier. 5-turn PHP made of copper capillary tube with inner diameter 1,1 mm was used as experimental sample. Main operational modes of PHP were defined and described in the paper based on obtained experimental data. Results indicate that increasing the heating zone length from 10 to 50 mm at all tested inclination angles significantly enhances the thermal performance of PHP by reducing start-up, transient heat flux densities and thermal resistance. Specifically, thermal resistance decreased by up to 51,8% and start-up, transient heat flux densities up to 68-71% with longer heating zone lengths. Also, it was shown that maximum transferred heat flux increased up to 59% with increasing in heating zone length. These findings suggest that optimizing heat zone length can improve start-up efficiency and overall heat transfer performance. The impact of inclination angle varies with the coolant used; generally, water outperforms methanol and pentane across all orientations. Methanol ranks next, with pentane showing the least performance. However, methanol and pentane are viable choices for low heat flux applications in vertical bottom heating mode. The study provides valuable insights for the design of PHP in energy, refrigeration and electronics cooling systems, highlighting the importance of heating zone (HZ) length configuration in achieving optimal performance